“Our Brommtopp is of Our Own Design”: (De)Constructing Masculinities in Southern Manitoba Mennonite Mumming - Fehr, Marcie; Greenhill, Pauline (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2011)
In the past and to some extent the present, various Euro North American and other cultural groups marked the period from Christmas Eve to Twelfth Night with rowdy, disguised, playful/ludic or carnivalesque behaviour that mainstream Euro North Americans associate more with Halloween than with this holiday season. Many such customs, termed the “informal house visit” involve a group (usually young men) who perambulate from one location to another within a community. They include performative aspects–often dancing and singing–as well as the expectation of a reward--usually food and/or drink--and some sociability with the visited household members. A seasonal custom performed by young men, almost always on New Year’s Eve, in rural Manitoba Mennonite villages where the church tolerated it, Brommtopp is named after the musical instrument used during the performance. Traditionally a group of some dozen teenaged boys and young married men would drive and/or walk from house to house within their own village and sometimes beyond. At each residence, the group would sing the traditional song which generally asked for money in return for good wishes. We examine the sociohistorical surround of the practice and its past and current racialised and postcolonial implications.